Outcome of Toxic Megacolon during Pregnancy - Carl Chartrand-Lefebvre; Jacques Heppell; Claude Potvin; Richard Clermont; Alfons Pomp (Canadian Journal of Gastroenterology)
Two patients with ulcerative colitis required subtotal colectomy and ileostomy for toxic megacolon during pregnancy. Subsequently, a mucosal proctectomy with ileal pouch-anal anastomosis was performed. These two patients who avoided permanent ileostomies were able to carry normal pregnancies and deliver normal infants. These two cases illustrate the clinical features and the favorable outcome of surgical treatment.